PERANCANGAN APLIKASI AUGMENTED REALITYKENDARAAN TEMPUR ALUTSISTA BERBASIS ANDROID - Ahmad Rizky Batubara; Mufida Khairani; Yunita Sari Siregar (LKP Unity Academy, 2024)
Augmented Reality (AR) is an environment that incorporates 3D virtual objects into a real environment. AR allows users to interact in real time. One of the implementations or applications of Augmented Reality technology is the introduction of the main weapons system tool (ALUTSISTA) utilizing media markers using 3D objects. There are three territorial types in military vehicle equipment, namely vehicles on land, air and sea. The introduction of types of military vehicles utilizing augmented reality using 3D objects was built using the SkethUp application to create 3D objects, the Vuforia Library as a marker database and the Unity3D Engine to build augmented reality